Love comes softly - Oke, Janette, 1935- (Oke, Janette, 1935- Love comes softly series, 2003)
Nineteen-year-old Marty Claridge, left alone and pregnant on the frontier prairie when her husband is killed in a tragic accident, goes to live with widower Clark Davis who needs someone to care for his young daughter and together they form a family based on faith, respect, and finally love.